Heatline Approach of Mixed Convection Inside Lid-Driven Cavity Having Heated Wall via Finite Element Method - Pang, Sui Liang (Enhanced Knowledge in Sciences and Technology, 2023)
In this study, mixed convection in lid driven cavity having heated wall is solved by COMSOL Multiphysics. The objectives of this study are display the isotherms, streamlines and heatlines within the cavity in different values of Reynolds number (Re) and Prandtl number (Pr), compare the results with earlier research and provide a suitable guideline for COMSOL Multiphysics 5.5. This study is showed the step by step in using COMSOL version 5.5 to create and to modify the streamlines, isotherms and heatlines plot of the heat transfer in lid-driven cavity. The results show that, that the streamlines and isotherms flow patterns are almost equal compare with the results of previous study but heatlines may have slightly different. For future work, the study can compare different values or situations in the streamline, isotherm and heatlines plot to enhance understanding of the heatline flows in mixed convection lid driven cavity.